Understanding the mechanical properties of self-expandable stents - Yoshino, Daisuke (Strojniški vestnik, 2008)
A medical device of mesh-shaped tubular structure called stent is frequently used to expand the constric-tion of a blood vessel. The stent normally has thestructure of longitudinal repetition of wavy wire parts and strut parts, and its mechanical properties such as bending flexibility and rigidity in radial direction mainly depend on the shape of wavy wire and construction of the strut. In the first stage of this paper, the mechanical properties of self-expandable stents are evaluated using a non-linear finite element method.The initial stent models are gener-ated in a 3D-CAD system, and their expanded shapes are predicted first. They form the finite elements for the evaluation of the mechanical properties, then the influences of stent shape onthe mechanical properties are com-puted and discussed. In the second stage, a basic method for the selection of a stent is proposed from a view point of mechanics. This enables us to select useful stents that are well adapted to a patient's condition, though medical examination is necessary.
Keywords: 3D CAD sistemi; biomehanika; stent; modeliranje; metode končnih elementov